Strategic Planning and Change Management in Telecommunication Industry in Kenya: Case Study of Telkom Kenya - Okeyo, Washington; Nyaera , Divinah Rachel (Archives of Business Research, 2020)
The purpose of the study was to examine the effect of strategic planning on change management in the telecommunication industry with the specific reference to Telkom Kenya Ltd. The study was anchored on Contingency Planning Theory. The target population was 1450 employees of Telkom Kenya. Stratified proportional sampling was used to get a suitable sample of 145 respondents and the study adopted a descriptive research design. Questionnaires were the main data collection tool and they were pilot tested on 15 staff at Telkom Thika branch before being administered to the target audience. Analysis of data was done using Statistical Package for Social Sciences Version 24. Descriptive statistics, specifically, means, averages and percentages were used to analyse individual variables. Simple tabulations were used to presented descriptive statistics. This study also used inferential statistics to examine the relationship between the study variables. Data was analysed using quantitative methods through regression analysis and presentation of data was in form of tables and figures. The study established that strategic planning had significant effect on change management. Specifically, the findings indicate that strategic planning and change management are positively and significantly related (R2= 0.57, p≤0.000). This study concluded that strategic planning plays an important role in change management such that change in the strategic planning results in positive variation in change management. The study recommended that, Telkom Kenya should treat strategic planning in the organization as one of the critical survival factors when implementing changes.